THE EFFECT OF CONCENTRATION OF CARRIER, pH AND TIME OF EXTRACTION ON SEPARATION'S FACTOR OF PENICILLIN G - PHENYL ACETATE BY REACTIVE EXTRACTION - Imam Santoso; Buchari Buchari; M. Bachri Amran; Aminudin Sulaeman (Universitas Gadjah Mada, 2007)
The aim of this research is to study the effect of concentration carrier, pH and time of extraction on separation's factor of penicillin g - phenyl acetate by reactive extraction technique. The 10 mL aqueous solution with variation of pH : 5, 6 contains 0.001 M penicillin G and 0.001 M phenyl acetate has been extracted with 10 mL n-butyl acetate contains dioctylamine as carrier. Variation concentration of carrier were 0.000; 0.002; 0.004; 0.006 and 0.008 M. Variation time of extraction were 1, 5, 10, 15 and 20 min. The penicillin G and phenyl acetate that dissolved in organic phase ha been reextracted with 10 mL aqueous with variation of pH : 7, 8. The optimum condition obtained as follow : concentration dioctylamine was 0.002M ; pH the first phase water was 5 and the second phase water was 8 ; and the time of extraction was 10 min.